Insight into interplay between PANoptosis and autophagy: novel therapeutics in ischemic stroke - Tian, He-Yan; Lei, Yun-Xing; Zhou, Jing-Tao; Liu, Long-Jun; Yang, Tong; Zhou, Yue; Ge, Jin-Wen; Xu, Chen; Mei, Zhi-Gang (Frontiers in Molecular Neuroscience, 2025)
PANoptosis is a novelly defined mode of programmed cell death that involves the activation of multiple cellular death pathways, including pyroptosis, apoptosis, and necroptosis, triggering robust inflammatory reactions. Autophagy is a crucial cellular process that maintains cellular homeostasis and protects cells from various stresses. PANoptosis and autophagy, both vital players in the intricate pathological progression of ischemic stroke (IS), a brain ailment governed by intricate cell death cascades, have garnered attention in recent years for their potential interplay. While mounting evidence hints at a crosstalk between these two processes in IS, the underlying mechanisms remain elusive. Therefore, this review delves into and dissects the intricate mechanisms that underpin the intersection of PANoptosis and autophagy in this devastating condition. In conclusion, the crosstalk between PANoptosis and autophagy in IS presents a promising target for the development of novel stroke therapies. Understanding the interplay between these two pathways offers a much-needed insight into the underlying mechanisms of IS and opens the possibility for new therapeutic strategies.